The Situation of the Education of Refugee Children in the Republic of Congo from1960-2017 - Castro, Boueya Fladimind; Oba, Dominique (Ridwan Institute, 2023)
Schooling is defined as the fact of schooling a child, that is to say, putting him on the school bench. It is actually compulsory for all children of school age. Due to its political stability, the Republic of Congo is a country that has received many refugees from Central African countries over the past twenty years. Since the return of peace to the Congo in 1998, after a period of turmoil and political instability, the Republic of the Congo has continued to attract many refugees from all directions. The practical application of the education of refugee children who have suffered war trauma is essential. National and international organizations are working in this sector to enable these children to have access to school education in Congo. They provide refugee children with various school supplies. Well educated, these refugee children help fight against illiteracy. Once schooled and trained, these children will be able to support themselves in the host country. On the other hand, the failure of their education would make them marginalized, embittered, bandits.